'Keep on Movin'', Everybody Soundsystem, Enjoy Public Art Gallery, Wellington, NZ - Galbraith H (Enjoy Public Art Gallery, Wellington New Zealand, 2022)
One of five texts commisioned in response to this collaboration by Gabby O'Connor, Jospehine Cachemaille, and Eve Armstrong, edited by Claire Harris. Text explores art works drawing on / responding to dance party culture in Aotearoa and internationally and responding to Everybody Soundsystem.
Keywords: contemporary art; collaboration; dance party culture